2016
DOI: 10.1556/036.103.2016.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lactate threshold using the modified Conconi test in distance runners

Abstract: This study aimed to examine the validity of the modified Conconi test (CT) to predict lactate threshold (LT) during running. Twelve distance runners randomly performed the modified CT and the incremental test in which LT was determined directly by measuring blood lactate (BLa). Mean values of heart rate (HR) and running speed (RS) at heart rate deflection point (HR DP ) obtained through the modified CT were compared with those at LT. Subsequently, the runners who showed a HR DP in the modified CT performed a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Furthermore, other studies reveal that the amount of hemoglobin in the blood is closely related to VO 2 max [23]. On the other hand, previous studies indicated that the administration of Moringa oleifera leaf extract could reduce lactate concentration [18]. This study related to the lactate threshold because decreasing lactic acid concentration will correlate with the lactate threshold.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, other studies reveal that the amount of hemoglobin in the blood is closely related to VO 2 max [23]. On the other hand, previous studies indicated that the administration of Moringa oleifera leaf extract could reduce lactate concentration [18]. This study related to the lactate threshold because decreasing lactic acid concentration will correlate with the lactate threshold.…”
Section: Discussionmentioning
confidence: 78%
“…PL/PJ.00.00/2022. Sixteen male athletes from West Java, Indonesia, were tested by the Balke test to measure VO 2 max and the modified Conconi test to measure lactate threshold [18]. In order to determine the muscle endurance capacity, the test of push up, sit up, and wall sit was administered to determine hand and shoulder muscle endurance, abdomen muscle endurance, and the extremities of inferior muscle endurance, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Ao avaliar corredores treinados de nível regional, Brunetta et al [21] observaram valores para o LAn determinado por meio do ponto de deflexão da FC de 11,4 ± 0,8 km•h-1. Em corredores de elite, Kjertakov et al [22] verificaram um LAn correspondente a 15,6 ± 0,7 km•h-1. Já para homens saudáveis, Nascimento et al [15] encontraram um valor de 9,2 ± 1,3 km•h-1 para o LAn determinado por meio do ponto de deflexão da FC.…”
Section: Resultsunclassified
“…This method, known as the Conconi method, link the lactic accumulation threshold with the HR dynamic change at high energy expenditure, appearing as an inflection point in the HR performance curve. Attractive by its simplicity, this approach suffers from several drawbacks, including a variable reliability 6,7 , the existence of HR performance curve having no inflection points [8][9][10] , and a lack of accuracy 11,12 .…”
Section: Introductionmentioning
confidence: 99%